INTERVENSI KEMANUSIAAN (HUMANITARIAN INTERVENTION) MENURUT HUKUM INTERNASIONAL DAN IMPLEMENTASINYA DALAM KONFLIK BERSENJATA - emi eliza; heryandi heryandi; ahmad syofyan (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
Humanitarian intervention is an attempt to prevent or stop the gross human rights violations with particular strengths (diplomatic and military) in a State, either with or without the consent of the State (countries with internal conflict). The problems in this journal are: first, how the arrangement of international law on humanitarian intervention. Secondly, the role of the UN in humanitarian intervention in armed conflicts. The method used is a normative legal research methods with the main source of data collection procedures is a legal substance that contains of normative law. The results showed that the rules of international law on humanitarian intervention by the United Nations stipulated in the UN Charter and general principles of international law. Humanitarian intervention legally justified by following provisions in applicable international law, namely Articles 39-51 of UN Charter. While the role of the UN in humanitarian intervention in armed conflicts carried out by the Security Council as the organ of the United Nations in maintaining peace with the decision issued in the form of a resolution for areas experiencing conflict. Therefore, it takes an international treaty that regulates clearly about humanitarian intervention, so that in practice, remain consistent with the objectives and executive organs of humanitarian intervention. Keywords: Humanitarian Intervention, Security Council of UN, Armed Conflict.